HUBUNGAN PRESTASI BELAJAR BIDANG SOSIAL MATERI TATAKRAMA BERMASYARAKAT DENGAN BIMBINGAN DAN KONSELING PADA SISWA KELAS VIII SMP N 1 RAMBAH - -, ERAWATI (Edu Research, 2015)
This research is motivated by the phenomenon that the authors see about a lot of students who are in dire need of guidance and counseling. This can be caused in people's lives and growing as it is today the problems faced by an increasingly complex society. So the guidance to children less priority. The purpose of this study is to how the provision of counseling and to find out how the class VIII student achievement SMP N 1 Rambah. In addition, it also aims to determine the relationship between the provision of counseling and learning achievement. The results showed that the provision of guidance counseling class VIII proved to exist and studentachievement is low. The result of the calculation is known that there is a significant relationship between the provision of guidance and learning achievement. It can be concluded that in order to improve learning outcomes can be done by streamliningpemberiamn counseling.